Mercado de trabalho dos jovens no Brasil entre 2018-2023 - Carmo, Mariele Santos do (2024)
The Brazilian labor market has undergone several changes in its dynamics and functioning in recent years, which have led to, among other things, an increase in unemployment and informality. When analyzing this issue, it was noted that young people, aged 14-24, have shown lower rates of participation in the labor market over the years. In this sense, this research described the participation of young people in the labor market, including their insertion in the period from 2018 to 2023. In addition, the work also considered variable aspects such as, for example, housing situation, level of education, employment position, among others. Thus, a bibliographical research was carried out on the subject, covering the dynamics of employment in the economy, as well as the participation of young people in the labor market, public incentive policies, and the specific case of young people who neither study nor work. This study is justified by analyzing the variables that refer to the participation of young people in the labor market ex-ante and ex-post to the Covid-19 pandemic. The analysis of the main results showed that the unemployment rate among young people is higher than that of the adult population, especially in the 20 to 24 age group, and that, although the pandemic has affected the labor market, even before the pandemic, these young people had difficulty finding jobs, especially formal jobs, often resorting to informal employment. Finally, there was a high rate of discouragement among young people and a decrease in the percentage of those who took some action to enter the market, showing the imminent need to develop specific policies aimed at training and entering this group into the labor market.